2014
DOI: 10.5603/cj.a2013.0085
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, anticoagulant treatment and risk of thromboembolism in patients with valvular atrial fibrillation: Results from Atrial Fibrillation in Turkey: Epidemiologic Registry (AFTER)

Abstract: (Cardiol J 2014; 21, 2: 158-162)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 21 publications
0
7
1
4
Order By: Relevance
“…On one hand, a considerable proportion of patients with embolic risk factors do not receive OAC therapy (13, 19), and on the other side, there is the problem of inappropriate combination of aspirin with warfarin, which ranges from 15% to 40% in the published literature (2,3,13,15-17), whereas it was 21.1% in our study. Perhaps more importantly, this practice occurs in patients with AF in the absence of firm evidence for clinical benefit.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…On one hand, a considerable proportion of patients with embolic risk factors do not receive OAC therapy (13, 19), and on the other side, there is the problem of inappropriate combination of aspirin with warfarin, which ranges from 15% to 40% in the published literature (2,3,13,15-17), whereas it was 21.1% in our study. Perhaps more importantly, this practice occurs in patients with AF in the absence of firm evidence for clinical benefit.…”
Section: Discussioncontrasting
confidence: 61%
“…The proportion of patients with MHV was high in our work probably because of a higher prevalence of rheumatic heart disease in our country compared with the western world (13). Recent Atrial Fibrillation in Turkey: Epidemiologic Registry reported 37% effective INR in patients with nonvalvular AF (14) and 36.1% effective INR in those with valvular AF, including MHV (15). In the present study, we found that 43.6% of all patients (43.2% in AF, 44.2% in MHV) had INR within the therapeutic range, which is slightly better.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indications and the prevalence of digoxin use are not well studied among Turkish patients with AF. The only Turkish multicentre study available including patients with AF was the AFTER study, which had shown that 27·7% of the patients were on digoxin therapy . However, the indications and appropriateness of digoxin use was not evaluated in the AFTER study.…”
Section: Introductionmentioning
confidence: 99%
“…The only Turkish multicentre study available including patients with AF was the AFTER study, which had shown that 27Á7% of the patients were on digoxin therapy. 11 However, the indications and appropriateness of digoxin use was not evaluated in the AFTER study. Therefore, we sought to investigate the prevalence, indications and appropriateness of digoxin prescription in a large, real-world population of Turkish patients with non-valvular AF (NVAF).…”
Section: Introductionmentioning
confidence: 99%